Postincident Interpersonal Difficulty Among Adolescent Victims of Violent Crime - Phillips, Jason B. (Journal of interpersonal violence, 2021)
Adolescents are exposed to high levels of violence in the United States. Exposure to violence at this point in the life course can have both short- and long-term consequences for young victims that include socioemotional distress and depression, substance abuse, and delinquency. Prior research indicates that positive, productive, and supportive reactions on the parts of those close to targets of violence attenuate feelings of distress and social anomie that many victims report. However, less attention has been devoted to the attributes of criminal violence that may stress the postincident interpersonal relationships of victims and their family members, friends, or peers. The disquieting effects of violence and bodily injury may influence how victims characterize their social connections in the wake of violent crime. This study uses data from the National Crime Victimization Survey (N = 1,652) to assess whether characteristics of violent acts and victims predict reports of postincident interpersonal difficulties made by violent crime victims aged 12 to 20. The findings are that more severe forms or levels of violence (e.g., robberies and sexual assaults) and reports of physical injuries are linked to perceptions of relationship difficulties with members of social networks by adolescent victims of violent crime. This study makes a contribution to our understanding of victimization by identifying levels of violence and injury as independent stressors on victims’ perceptions of their relationships and as relevant components of how younger victims see themselves or are perceived by others. It also represents a direct test of whether attributes of violent acts undermine adolescents’ perceptions of the quality of their relationships. The results of the study could also aid in the development of interventions that better address the needs of both young victims and their supporters.